Evaluating Performance of Supply Chain Management System: A Conceptual Analysis in BSNL - Akshaya Kumar Sahoo; Dr. Uma Sankar Mishra (International Journal of Supply Chain Management, 2013)
The problems in the telecom service industry arequite visible now a days and the pace of new technology development within thisindustry is extremely high. The telecom industry is selected for review,analysis and research because it is of fast changing, multiple product variantand high volume business environment with a lot of focus on new technologydevelopment and speedy implementation of new ideas and innovations in to newproducts. Especially, BSNL has taken for focus area because it has a secondmajor market share in Indian market along with its sister concern publicsectors like MTNL (Mahanagar Telecom Nigam Limited) and TCIL (TelecomCorporation of India Limited). The scope of this research is to studyoptimizing availability of both new existing, and multiple verifiedtechnologies. The literature review highlighted in this paper discusses somemajor issues and challenges in supply chain management system. In this context,this paper aims at relating the theories and principles of supply chainmanagement system that could be used in practice in the telecom serviceindustry especially in BSNL. The paper presents comparisons between themanufacturing and the telecom service industry with special reference to BSNL,a public sector of Govt. of India. The comparison resulted that SCM is wellcontained in any service sector may be private or public sector.